(untitled) (Scientific journal of the Fergana State University, 2023)
In this article theoretical aspects of linguistic image of the world and scientific image of the world are learned. Factors, conditions and opinions on linguistic image of the world are analyzed. Linguistic image of the world and scientific image of the world are compared.